Sistem Pakar Diagnosa Penyakit THT Menggunakan Inferensi Forward Chaining dan Metode Certainty Factor - Dirgantara, Bhintang; Hairani, Hairani (Jurnal Bumigora Information Technology (BITe), 2021)
Currently, Ear, Nose, and Throat (ENT) has become a disease that is quite common in the world. In Indonesia, people with ENT disease are around 190-230 per 1000 population. The types of diseases studied in this study were Serous Orthitis Media, Nasal Polyps, Acute Pharyngitis, Retrofaryngeal Abscess, and Nafosaryngeal Carcinoma. The purpose of this study was to make an application of an expert system for the diagnosis of ENT diseases using forward chaining inference and certainty factors that can facilitate medical personnel to diagnose types of ENT diseases. The stages of developing an expert system in this study consisted of problem identification for problem domain, knowledge acquisition was used to obtain the MB and MD value of each symptom in ENT disease with the interview method, the design was used to design knowledge representations such as decision tables and inference engine. With the expert system of ENT disease diagnosis, it can make it easier for doctors to make decisions, or the right diagnosis of a symptom that arises in ENT, so that proper treatment is obtained and minimizes the occurrence of misdiagnoses